The Influence of Islamic Financial Literacy and Service Ease of Use on Customers’ Decisions to Use Islamic Digital Banking Products with Islamic Financial Inclusion as a Mediating Variable - Sari, Silvia Novita; Sholahuddin, Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of Islamic financial literacy and the ease of use of digital services on customers’ decisions to use Islamic digital banking products, with Islamic financial inclusion as a mediating variable. The research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to Islamic bank customers who use digital services in Indonesia. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4 software. The results indicate that Islamic financial literacy and the ease of use of digital services have a positive and significant effect on customers’ decisions to use Islamic digital banking products. In addition, both variables also have a positive and significant influence on Islamic financial inclusion. Islamic financial inclusion, in turn, has a positive effect on customers’ decisions and is able to mediate the relationship between Islamic financial literacy, the ease of use of digital services, and the decision to use Islamic digital banking products. The novelty of this study lies in the development of an integrative research model that combines Islamic financial literacy and the ease of use of digital services by incorporating Islamic financial inclusion as a mediating variable within the context of digital Islamic banking. This study is expected to enrich academic literature on customer decision behavior and provide practical implications for Islamic banking institutions in enhancing inclusive and sustainable digital service adoption.